Management Fisioterapi untuk Penangganan Cedera Olahraga Sprain Ankle : Case Report - Yngvie Salma Kirani; Totok Budi Santoso; Hakny Maulana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Ankle sprain is a tearing or rupture injury that occurs in the ligaments, especially the lateral part, which triggers joint instability, causing pain, disrupting functional activities and reducing the athlete's ability. The purpose of this study was to determine the management and effectiveness of physiotherapy interventions carried out in cases of ankle sprains. the study used a case report with single subject research, observing a patient, Mr. S, aged 27 years who complained of pain and swelling in the ankle due to a sports injury. The study was conducted in December 2024. Physiotherapy was carried out every 3 days, 3 times with ultrasound intervention, ice compresses, TENS and exercise therapy in the form of ankle theraband, calf raise, toe curl with towel, and marble pick-up. Results: This study showed periodic improvements in T0 to T3 as seen from several aspects such as pain evaluated using NRS, increased ROM measured using a goniometer, decreased edema evaluated with the midline, and improved functional ability evaluated with FAAM. Treatment of ankle sprain with ultrasound modality, ice compress, TENS and exercise therapy in the form of ankle theraband, calf raise, toe curl with towel, and marble pick-up can reduce pain, increase LGS, reduce swelling, and improve functional activities in ankle sprain patients.